DIAGNOSTIC ALGORITHM FOR CLARIFYING INTRADUCTAL PAPILLOMA WITHOUT GALACTOGRAPHY - Aliyeva, H.N.; Amirova, M.F.; Melikova, N.V.; Guliyeva, F.E.; Hasanov, V.M.; Rahimov, J.A. (World of Medicine and Biology, 2025)
Intraductal papilloma is a benign proliferative lesion of the mammary ducts that can mimic malignancy on clinical and radiological grounds. While galactography is typically used for evaluation, its absence can delay diagnosis. We present a case study of a 35-year-old woman with typical intraductal papilloma symptoms but without access to galactographic evaluation. Diagnosis relied on alternative modalities, including ultrasonography, digital breast tomosynthesis, and MRI, followed by histopathological confirmation. Initial imaging revealed a hypo-echoic lesion with irregular margins and no vascular signals. Subsequent ultrasonography revealed a hyper-echoic intraductal focus. Digital breast tomosynthesis was inconclusive, while MRI showed non-mass enhancement categorized as BI-RADS 4. Histological analysis confirmed a solitary intraductal papilloma with no atypia or malignancy. This case highlights that in the absence of galactography, a structured diagnostic pathway incorporating ultrasonography, digital breast tomosynthesis, and MRI can effectively identify intraductal papilloma. Early recognition and multidisciplinary assessment are essential to avoid misdiagnosis and ensure timely management.
Keywords: galactography-lack circumstances; Intraductal papilloma; magnetic resonance imaging; ultrasonography; tomosynthesis